2023
DOI: 10.1111/ajd.14120
|View full text |Cite
|
Sign up to set email alerts
|

Double vision due to lateral rectus injury after cosmetic botulinum toxin injections

Abstract: Facial intramuscular injections of Botulinum toxin (BoNT) injections are among the most common cosmetic procedures in dermatology. Rarely, serious adverse reactions such as blepharoptosis, diplopia and periorbital hematoma may occur with improper administration technique. Here we report a case of painless diplopia 5 weeks post‐BoNT injection for ‘crow's feet’ likely due to inadvertent BoNT diffusion into the lateral rectus muscle causing a temporary palsy. This case aims to raise awareness of proper cosmetic B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…This will reduce the potential for the neurotoxin to diffuse through the orbital septum (Delle Chiaie, 2024; Witmanowski & Błochowiak, 2020). Khan et al (2023) suggested that if a neurotoxin is inadvertently injected into the arteries supporting the lateral canthus it could allow diffusion of the toxin into the extraocular muscles, via the vascular system.…”
Section: Injection Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This will reduce the potential for the neurotoxin to diffuse through the orbital septum (Delle Chiaie, 2024; Witmanowski & Błochowiak, 2020). Khan et al (2023) suggested that if a neurotoxin is inadvertently injected into the arteries supporting the lateral canthus it could allow diffusion of the toxin into the extraocular muscles, via the vascular system.…”
Section: Injection Techniquementioning
confidence: 99%
“…In most cases, the diplopia is caused by a weakened extraocular muscle. When the diplopia is accompanied by a palsy, it is generally caused by a complete paralysis of the involved muscle (Delle Chiaie, 2024; Khan et al, 2023; Scott et al, 2023).…”
mentioning
confidence: 99%